Efficacy comparison between intramedullary nail fixation and plate fixation in distal tibia fractures: a meta-analysis of randomized controlled trials - Xiaobin Li; Kaipeng Chen; Haipeng Xue; Junwen Cheng; Xiaoping Yu (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Background Intramedullary nail (IMN) and plate fixation are the most commonly used surgical modalities for distal tibia fractures. However, the superiority of their efficacy regarding functional outcomes and complications remains controversial. Here, we performed a systematic review and meta-analysis to compare the efficacy of these two modalities. Methods Randomized controlled trials (RCTs) comparing the efficacy of IMN and plate fixation in distal tibia fractures were searched in PubMed, Web of Science, EMBASE, ClinicalTrials.gov, and Cochrane Library up to January 31, 2024. Weighted mean difference (WMD) and odds ratio (OR) with corresponding 95% confidence interval (CI) were estimated using a random-effect model for continuous and categorical outcomes, respectively. Results A total of 20 RCTs comprising 1528 patients were included. Compared with plate fixation, IMN significantly shortened surgery time (WMD=-10.73 min, 95%CI: -15.93 to -5.52), union time (WMD=-1.56 weeks, 95%CI: -2.82 to -0.30), and partial (WMD=-1.71 weeks, 95%CI: -1.91 to -0.43) and full (WMD=-2.61 weeks, 95%CI: -3.53 to -1.70) weight-bearing time. IMN was associated with markedly reduced risk of wound infection (OR = 0.44, 95%CI: 0.31–0.63) and secondary procedures (OR = 0.72, 95%CI: 0.55–0.95), but increased the risk of malunion (OR = 1.53, 95%CI: 1.02–2.30) and anterior knee pain (OR = 3.94, 95%CI: 1.68–9.28). The rates of nonunion, delayed union, and functional assessment scores did not significantly differ between the two groups. The percentages of patients obtaining an excellent functional outcome or an excellent and good functional outcome post-operation were comparable. Conclusions Both IMN and plate fixation are effective modalities for the surgical treatment of distal tibia fractures. IMN seems to be preferred since it confers more advantages, but the elevated rates of malunion and knee pain require attention. The decision on fixation modality should be tailored to the specific fracture, considering these pros and cons.